Correlation between body mass index and gender-specific 28-day mortality in patients with sepsis: a retrospective cohort study - Li, Chong; Huang, Huaping; Xia, Qingjie; Zhang, Li (Frontiers in Medicine, 2024)
Objective To investigate the potential correlation between body mass index (BMI) and the 28-day mortality rate among sepsis patients and the gender difference in this association. Design The current research was a retrospective cohort study. Participants A total of 14,883 male and female cohorts of sepsis patients were included in the Medical Information Mart for Intensive Care IV (MIMIC-IV V2.2) database. Patients in each gender cohort were further classified as underweight, normal weight, overweight, or obese according to BMI and the World Health Organization (WHO) BMI categories. Outcomes The 28-day mortality from the date of ICU hospitalization was the primary outcome measure. Results The BMI and 28-day mortality exhibited an L-shaped relationship (p for nonlinearity <0.001) with significant gender-specific differences. Subgroup analysis revealed different association patterns between the male and female cohorts. Specifically, BMI and mortality exhibited a U-shaped curve relationship among the males (p for nonlinearity <0.001) and an L-shaped relationship among the females (p for nonlinearity = 0.045). Conclusion This study proposes a link between extreme BMI and 28-day mortality in patients with sepsis. Underweight patients have an increased risk of mortality; however, this risk decreases in overweight and obese patients. Upon stratifying by sex, a U-shaped pattern was observed, indicating an association between BMI and 28-day mortality in males, while an L-shaped pattern emerged in females.